Topology control scheme based on simulated annealing algorithm in wireless sensor networks - LIU Lin-feng; LIU Ye (Tongxin xuebao)
In order to study the topology control scheme satisfying the requirement of lifetime objective in wireless sen-sor networks and aiming at the defect that high redundancy of connectivity or low robust of structure in traditional schemes, the desire of topology was modeled and analyzed theoretically. The model was transformed into a problem of degree-constrained minimum spanning tree ultimately, and a simulated annealing algorithm was designed to deal with the problem. A topology control scheme was proposed based on simulated annealing algorithm. The scheme was analyzed and validated for performance through experiments. The result suggests that a topology with low total power consumed, high robust structure and low contention that can be controlled among nodes, and the lifetime of networks can be pro-longed on the topology.